State of knowledge of the Glomeromycota of Costa Rica - De Jesús Alarcón, María Mabel (2025)
Introduction: Arbuscular mycorrhizal fungi (AMF) play a pivotal role in plant nutrition and soil stability, also play an important role for sustainable agriculture and the restoration of degraded areas. In Costa Rica, research has been conducted on the diversity of AMF in select ecosystems. However, a comprehensive compilation of these studies is currently lacking. Objective: To compile an updated list of arbuscular mycorrhizal fungi (AMF) in Costa Rica, organised by vegetation types and life zones. This will facilitate a more comprehensive understanding of their diversity and serve as a foundation for future research in taxonomy, distribution, ecology and biotechnological applications. Methods: A comprehensive literature search was conducted in Google Scholar, Scopus and Web of Science, utilising Spanish and English terms related to arbuscular mycorrhizal fungi (AMF) and Costa Rica, spanning the period from 1971 to 2024. The selection criterion included studies that identified species based on morphological or molecular criteria. The following information was integrated into a database. Results: We compiled 57 studies published from 1975-2024 and after screening 549 initial records, 115 records corresponding to species level were confirmed. 60 AMF species belonging to five orders were identified, representing 16 % of the global diversity known as Glomeromycota. The families Glomeraceae (23 species) and Acaulosporaceae (19 species) were the best represented. Furthermore, it was observed that studies have been conducted in only four of the 12 life zones described for Costa Rica, and include agroecosystems and trap crops (consortia) or pure crops (monospecific). Conclusions: It is evident that there has been a degree of advancement in the comprehension of the ecology, diversity and distribution of AMF. Nevertheless, further ecological and taxonomic research is required, encompassing both morphological and molecular analyses, to facilitate the expansion of knowledge concerning the distribution and diversity of AMF in Costa Rica.